Mitochondrial NNT promotes diastolic dysfunction in cardiometabolic HFpEF - Pepin, Mark; Konrad, Philipp; Nazir, Sumra; Bazgir, Farhad; Maack, Christoph; Nickel, Alexander; Gorman, Joshua M.; Hohl, Mathias; Schreiter, Friederike; Dewenter, Matthias; de Britto Chaves Filho, Adriano; Schulze, Almut; et al. (Circulation research, 2025)
BACKGROUND: - Clinical management of heart failure with preserved ejection fraction (HFpEF) is hindered by a lack of disease-modifying therapies capable of altering its distinct pathophysiology. Despite the widespread implementation of a 2-hit model of cardiometabolic HFpEF to inform precision therapy, which utilizes HFD+L-NAME (ad libitum high-fat diet and 0.5% N[ω]-nitro-L-arginine methyl ester), we observe that C57BL6/J mice exhibit less cardiac diastolic dysfunction in response to HFD+L-NAME. - METHODS: - Genetic strain-specific single-nucleus transcriptomic analysis identified disease-relevant genes that enrich oxidative metabolic pathways within cardiomyocytes. Because C57BL/6J mice are known to harbor a loss-of-function mutation affecting the inner mitochondrial membrane protein Nnt (nicotinamide nucleotide transhydrogenase), we established an isogenic model of Nnt loss-of-function to determine whether intact NNT is necessary for the pathological cardiac manifestations of HFD+L-NAME. Twelve-week-old mice cross-bred to isolate wild-type (Nnt+/+) or loss-of-function (Nnt−/−) Nnt in the C57BL/6N background were challenged with HFD+L-NAME for 9 weeks (N=6-10). - RESULTS: - Nnt+/+ mice exhibited impaired ventricular diastolic relaxation and pathological remodeling, as assessed via noninvasive echocardiographic quantification of early diastolic pulse-wave velocity (E) to mitral annular velocity (e′) ratio (E/e′) (42.8 versus 21.5, P=1.2×10−10), E/A (early-to-late mitral inflow velocity ratio) (2.3 versus 1.4, P=4.1×10−2), diastolic stiffness (0.09 versus 0.04 mm Hg/μL, P=5.1×10−3), and myocardial fibrosis (P=2.3×10−2). Liquid chromatography and mass spectroscopy exposed a 40.0% reduction in NAD+ (P=8.4×10−3) and a 38.8% reduction in the ratio of reduced-to-oxidized glutathione (GSH: GSSG, P=2.6×10−2) among Nnt+/+ mice after HFD+L-NAME feeding. Using single-nucleus ligand-receptor analysis, we implicate Fgf1 (fibroblast growth factor 1) as a putative NNT-dependent mediator of cardiomyocyte-to-fibroblast signaling in myocardial fibrosis. - CONCLUSIONS: - Together, these findings underscore the pivotal role of mitochondrial dysfunction in HFpEF pathogenesis, implicating both NNT and Fgf1 as novel therapeutic targets.
Online veröffentlicht: 9. Mai 2025
Gesehen am 23.09.2025